Anti-Inflammatory and Anticoagulant Activities of Synthesized NSAID Prodrug Esters. (26th May 2020) - Abualhasan, Murad N.; Al- Masri, Motasem Y.; Manasara, Rufaida; Yadak, Lana; Abu-Hasan, Nael S.
Abstract : Paracetamol with ibuprofen or with naproxen are frequently prescribed by doctors in combination. It was found that patients using a combination of NSAID like acetaminophen and ibuprofen experienced less pain. Patients are more compliant if these two drugs are combined in an ester form and given in one dosage form. The esterified prodrugs are hydrolyzed in humans to their active forms. In this study, two esters of paracetamol combined with ibuprofen and naproxen were synthesized as prodrugs. The physiochemical properties of these products were identified. Moreover, the bioactivities of these prodrugs were tested for its anti-inflammatory and anticoagulant activities. The results showed an improved COX inhibition and anticoagulant activity compared with their parent drugs. The synthesized drugs are expected to improve patient's compliance in terms of administration frequency and will have better pharmacokinetic properties with fewer side effects.